STABILITAS SENYAWA FENOLIK DALAM EKSTRAK DAN NANOKAPSUL KELOPAK BUNGA ROSELLA PADA BERBAGAI VARIASI pH, SUHU DAN WAKTU - Ike Sitoresmi M Purbowati; Khaswar Syamsu; Endang Warsiki; Herastuti Sri (Agroindustrial Technology, University of Trunojoyo Madura, 2016)
The extract which is still in liquid form, has several weaknesses, such as unstable in enviroment changes, low flexibility uses and trouble in material handling and transportation. For these reasons, nanoencapsulation technique using β-siklodextrin as matrix agent is an alternative way. The aims of this research were characterization of total phenols, antioxidant activity of nanoencapsulation and the stability of the extract as well as nanocapsules against the changes of pHs, temperatures and boiling times. Nanocapsules of roselle extract was containing phenol 4,53 + 0,26 mg/g, anthocyanin 2,99 + 0,18 mg/g, vitamin C 2,77 + 0,04 mg/g and water moisturizer 5,16 + 0,03%, antioxidant activity 49%. Nanocapsules more resistence against the enviroment changes than the extract itself. The stability test against the enviroment changes, the nanocapsules form more stable than the extract. Showed with the slope of linier regression of nanocapsules form for phenols and antioxidant activity, respectively were: 0,111; 1,307 lower than the extract : 2,825; 7,634. Nanocapsules more resistence against temperature and boiling time than the extract itself. The stability test against temperature and boiling time, the nanocapsules form more stable than the extract. Showed with the slope of linier regression of nanocapsules for phenols and antioxidant activity respectively were: 1,3315; 0,3162 lower than the extract : 1,5864; 0,5389